Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Help me with that problem, please.

$$\lim_{x \to 0}\left ( \frac{1}{x^{2}}-\cot x\right )$$

share|cite|improve this question
use that $\cot x = \frac{\cos x}{\sin x}$ and for the latter functions you know that $\sin x \sim x$ and $\cos x \sim 1-\frac12x^2$ at $x = 0$. And since this is homework, what have you tried? – Ilya Mar 22 '12 at 16:28
I tried Lopital rule, but not sure that is right – Unbelievable Me Mar 22 '12 at 16:36
Are you sure you don't mean $\cot^2x$? – anon Mar 22 '12 at 16:49
@anon Yes I am sure – Unbelievable Me Mar 22 '12 at 16:56
Then the limit does not exist. If it was $\cot^2x$ instead of $\cot x$ then the limit would be 2/3, and if it was $1/x$ instead of $1/x^2$ the limit would 0. – anon Mar 22 '12 at 17:06

$$\lim\limits_{x \to 0} \left(\frac{1}{x^2} - \frac{1}{\tan x}\right) = \lim\limits_{x \to 0} -\left( \frac{x^4 \tan x - x^2 \tan^2 x}{x^4 \tan^2 x}\right) = -\lim\limits_{x \to 0} \frac{(x^2\tan x)(x^2-\tan x)}{(x^2 \tan x)(x^2 \tan x)}$$

Cancelling out terms:

$$-\lim\limits_{x \to 0} \frac{x^2 - \tan x}{x^2 \tan x}$$

Apply L'Hopitals Rule

$$-\lim\limits_{x \to 0}\frac{x \cos2x + x - 1}{x(x+\sin 2x)} =-\frac{\lim\limits_{x \to 0}x + \lim\limits_{x \to 0}x \cos 2x - 1}{\lim\limits_{x \to 0}x(x+\sin 2x)} =-\frac{-1}{\lim\limits_{x \to 0}x(x+\sin2x)}$$

The limit of the products is the product of the limits.

$$\frac{1}{\lim\limits_{x \to 0}x(x+\sin2x)} = \frac{1}{(\lim\limits_{x \to 0}x)(\lim\limits_{x \to 0}(x + \sin 2x))}$$

Since $\lim\limits_{x \to 0}x = 0$,

$$\lim\limits_{x \to 0} = \left(\frac{1}{x^2} - \cot x\right) = \infty$$

share|cite|improve this answer

$$\lim_{x\rightarrow 0} \left(\frac{1}{x^2}-\frac{\cos x}{\sin x}\right)=\infty,$$


$$\lim_{x\rightarrow 0} \left(\frac{1}{x^2}-\frac{\cos^{2}x}{\sin^{2}x}\right)=\frac{2}{3}.$$

share|cite|improve this answer
can you prove the second one ,please? – Razvan Paraschiv Jul 29 '15 at 0:33

Note that for $x>0$ near $0$ we have $$ \frac{1}{x^2} - \cot x = \frac{1}{x^2}-\frac{\cos x}{\sin x} \geq \frac{1}{x^2}-\frac{1}{\sin x} = \frac{\sin x - x^2}{x^2 \sin x}. $$

Then we have $$ \lim_{x\to 0^+}\frac{\sin x - x^2}{x^2 \sin x} \ \operatorname*{=}^{\small\mathrm{L'H}}\ \lim_{x\to 0^+} \frac{\cos x-2x}{2x\sin x + x^2\cos x } = \infty $$ so it follows by the squeeze theorem that $$ \lim_{x\to 0^+}\left(\frac{1}{x^2} - \cot x \right) = \infty. $$

For $x<0$ near $0$ we have $\cot x < 0$ so $$\frac{1}{x^2}-\cot x \geq \frac{1}{x^2} \to \infty$$ and so

$$ \lim_{x\to 0}\left(\frac{1}{x^2} - \cot x \right) = \infty. $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.